Sexual risk factors for partner age discordance in adolescent girls and their male partners. Issue 23 (December 2013) - Morrison‐Beedy, Dianne; Xia, Yinglin; Passmore, Denise
Abstract : Aims and objectives: To investigate differences in sexual risk factors between adolescent girls reporting similar‐aged or older sex partners. Background: Adolescent girls are at significant risk of heterosexual‐acquired HIV infection and other long‐term reproductive health issues. Sexual partner age discordance in teen girls has been correlated with STIs, lack of protection, multiple partners and earlier age of sexual transition. Design: A descriptive study comparing girls currently involved with age‐discordant partners to those with similar‐aged partners. Two‐sample t‐test for continuous variables and chi‐squared test or Fisher's exact test for categorical variables were used to compare groups. Methods: Baseline data from 738 sexually active, urban, adolescent girls aged 15–19 were analysed to determine which behaviours were more likely to occur in girls with older partners. Data were collected as part of a gender‐specific HIV‐prevention intervention in a randomised controlled trial (RCT) tailored to adolescent girls. Results: Multiple reported sexual risk behaviours were found to significantly differ between the two groups at baseline. Overall, girls with older partners had more episodes of sexual instances (vaginal, anal and oral). Specific sexual risk behaviours were found to be statistically significant between the two groups. Girls with older partners started having sex at earlier ages, had more lifetime sexual partners, higher incidents of STIs and were reluctant to discuss using condoms with their partners. Girls with similar‐aged partners were less willing to engage in risky sexual behaviours. Conclusions: Findings from this investigation support data from other studies. Relationships with older male partners place adolescent girls at increased risk of HIV/STIs and unintended pregnancy. Relevance to clinical practice: Adolescent girls in age‐discordant relationships are at risk of immediate and long‐term sexual health morbidities. Identifying girls who are at increased risk by asking tailored questions will enable nurses to recommend appropriate diagnostics for this population and provide age‐specific counselling.